Preparation and Mechanism of a New Enhanced Flocculant Based on Bentonite for Drinking Water - Feng-shan Zhou; Jie Li; Lin Zhou; Yang Liu (Advances in Materials Science and Engineering)
Bentonite is characterized by the large specific surface, good adsorption, ion exchange ability, and nontoxicity. An enhanced bentonite base composite flocculant (BTA) can be prepared from treating the calcium base bentonite and compositing various functional additives. Bentonite was firstly treated by citric acid, then the talc and activated carbon turned to be acid part and simultaneously the part that was treated by sodium bicarbonate and calcium hydroxide turned to be alkaline part, and finally the acid bentonite part and alkaline bentonite part were mixed up with preground powder of polymeric chloride aluminium (PAC), cationic polyacrylamide (CPAM), ferrous sulfate, and aluminum sulfate, and after all of the processing flocculant BTA was obtained. The optimum preparation process of flocculant BTA has shown 29.5% acid bentonite part, 29.5% alkaline bentonite part, 15% PAC, 1% CPAM, 5% ferrous sulfate, and 20% aluminum sulfate. BTA was used to treat drinking water with high turbidity and metal ion in Karamay City, Xinjiang. The treated water was surely up to the drinking water standard of China in decolorization rate, deodorization rate, heavy metal ion removal rate, and so forth, and contents of residual aluminum ions and acrylamide monomer in drinking water were considerably decreased.